2011
DOI: 10.3899/jrheum.110705
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated with Relapse in Japanese Patients with Microscopic Polyangiitis

Abstract: In Japan, relapse of MPO-ANCA-positive MPA may be associated with the reduction rate of oral prednisolone administration during maintenance therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 21 publications
(39 reference statements)
0
15
0
Order By: Relevance
“…However, it is highly controversial whether fast tapering of GC is associated with increasing risk of relapse in AAV patients. While some studies supported this notion [ 26 , 27 ], it has recently been demonstrated that GC therapy beyond 6 months is associated with a greater risk of infections, but not with a decreased risk of relapse [ 24 ]. The incidence of SIs in the present study was notably higher than those in previous observational studies from European countries [ 24 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is highly controversial whether fast tapering of GC is associated with increasing risk of relapse in AAV patients. While some studies supported this notion [ 26 , 27 ], it has recently been demonstrated that GC therapy beyond 6 months is associated with a greater risk of infections, but not with a decreased risk of relapse [ 24 ]. The incidence of SIs in the present study was notably higher than those in previous observational studies from European countries [ 24 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…One recent underpowered retrospective study compared the relapse rate of patients who were cANCA-positive or cANCA-negative at the time of remission and found no significant difference in relapse risk [24]. The significance of persistent MPO-ANCA at the time of switch to maintenance therapy was investigated in 62 Japanese patients with MPA and was not found to be associated with an increased risk of relapse, although several studies have reported an increased risk of relapse associated with an increase in MPO-ANCA titre once in remission [9, 25]. Rituximab is now increasingly being used for both remission induction and maintenance in AAV.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that the persistence of PR3-ANCA, but not MPO-ANCA, at the time of discontinuing cyclophosphamide and switching to maintenance therapy is associated with an increased risk of relapse [7, 9]. We used long-term follow-up data from two of the previous European Vasculitis Study Group (EUVAS) clinical trials, CYCLOPS and IMPROVE, to identify whether persistent ANCA positivity at the time of discontinuing cyclophosphamide and switching to maintenance therapy is associated with an increased risk of relapse in patients with moderate-to-severe ANCA-associated vasculitis (AAV) treated with cyclophosphamide as initial remission induction therapy [10, 11].…”
Section: Introductionmentioning
confidence: 99%
“…Since 2008, we have conducted a retrospective cohort study elucidating risk factors associated with relapse in microscopic polyangiitis (MPA) patients [ 1 ] and a nationwide epidemiologic study of eosinophilic granulomatosis with polyangiitis. The clinical studies described below are in progress currently.…”
Section: The Research Committee On Intractable Vasculitides the Minimentioning
confidence: 99%
“…Based on our retrospective study elucidating the risk factors for relapse in patients with myeloperoxidase (MPO)-ANCA positive MPA [ 1 ], we are conducting an observational cohort study of remission maintenance therapy in Japanese AAV patients (Co-RemIT-JAV) (UMIN000006373). The study objective is to clarify the safety and efficacy of remission maintenance therapy in Japanese AAV patients.…”
Section: Co-remit-javmentioning
confidence: 99%